(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article provides an introduction to the study of metaphorical models in linguistics. The opinions and views of scientists about the metaphorical model are reflected. When studying metaphor as a semantic model in modern metaphorology, the problem of division into lexical-semantic, thematic groups is considered.